2010
DOI: 10.1042/bj20100637
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of PRG-1 as a neuronal calmodulin-binding protein

Abstract: Intracellular Ca2+-dependent cellular responses are often mediated by the ubiquitous protein CaM (calmodulin), which, upon binding Ca2+, can interact with and alter the function of numerous proteins. In the present study, using a newly developed functional proteomic screen of rat brain extracts, we identified PRG-1 (plasticity-related gene-1) as a novel CaM target. A CaM-overlay and an immunoprecipitation assay revealed that PRG-1 is capable of binding the Ca2+/CaM complex in vitro and in transfected cells. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 45 publications
0
35
0
Order By: Relevance
“…PRG-1 is highly expressed in the forebrain and in the cerebellar cortex (30). It has been reported that overexpression of PRG-1 induces neurite outgrowth in PC12 cells (36) and that PRG-1 is up-regulated during periods of axonal outgrowth and attenuates LPA-induced axon collapse (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PRG-1 is highly expressed in the forebrain and in the cerebellar cortex (30). It has been reported that overexpression of PRG-1 induces neurite outgrowth in PC12 cells (36) and that PRG-1 is up-regulated during periods of axonal outgrowth and attenuates LPA-induced axon collapse (27).…”
Section: Discussionmentioning
confidence: 99%
“…PRG-1 is an important molecule in the control of hippocampal excitability dependent on presynaptic LPA 2 receptor signaling (29). PRG-1 is likely to be a calmodulin (CaM)-interacting protein and is involved in postsynaptic functions regulated by intracellular Ca 2ϩ signaling (30). Deletion of Prg-1 in mice leads to epileptic seizures and augmentation of excitatory postsynaptic current (EPSC) but not inhibitory postsynaptic current (IPSC) (29).…”
mentioning
confidence: 99%
“…Prg1 is a neuronal calmodulin‐binding protein that regulates intracellular calcium signaling (Tokumitsu et al, ). Calmodulin seems to be a key effector in calcium‐related cell survival (Gallo et al, ; Boutillier et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Other Methods-The CaM overlay method was performed using 0.5 g/ml biotinylated CaM in the presence of 1 mM CaCl 2 , followed by detection of the CaM-binding signal using a chemiluminescence reagent (PerkinElmer Life Sciences) as described previously (28). Protein concentration was estimated by staining the samples with Coomassie Brilliant Blue (BioRad) using bovine serum albumin as a standard.…”
Section: Methodsmentioning
confidence: 99%